Perbandingan Kemampuan Dan Kemauan Membayar Peternak Non Biogas Di Dusun Krajan, Desa Pujon Kidul - Octariana, Tiara; Meidiana, Chistia; Hidayat, AR Rohman Taufiq (Fakultas Teknik, Universitas Brawijaya, 2016)
The development of alternative energy can be applied by any community, especially farmers in the village, considering the potential of livestock in Indonesia which reached 16.019 million. Farmers can perform the processing of manure waste to independent energy fulfillment by the community. In the development of independent energy fulfillment, it takes charge of the community for its implementation. The purpose of this study is assessed the benefit of using biodigester. The value of such interest is to view at the balance of interests of the use of biodigester and costs incurred by the farmers. Pujon Kidul village has a great potential in utilizing livestock manure. Pujon Kidul village has 453 farmers with the total of 1,390 farmers, but the manure management is still limited. This is because farmers have problems in costs, whereas if the farmer does not have enough income, the farmers are less likely to build a biodigester. Therefore, this reasearch is conducted to see the ability and willingness to pay of the farmers. Then, its compared in order to get the value of interests. This study is using analysis of ability to pay and willingness to pay. From the comparison, as many as 93% farmers have a greater willingness to pay of his ability (choice riders), it indicates the need for a biodigester is very important for farmers.Keywords: biodigester, ability to pay, willingness to pay